Centrifuge modelling of tunnelling induced ground displacements: pressure and displacement control tunnels. (September 2020) - Song, Geyang; Marshall, Alec M.
Highlights: Tunnelling induced ground movements for pressure and displacement control tunnels. Centrifuge test results of greenfield tunnelling in sands. Calibration of hypoplastic constitutive model for numerical analysis. Soil volumetric and shear strain distribution due to tunnel volume loss. Abstract: Predicting the impact of tunnelling-induced ground movements on existing foundation systems or infrastructure is an important stage during tunnel design or risk assessment processes. Centrifuge modelling has been used extensively as a tool to study soil movements caused by tunnelling and their interactions with existing structures. In 2D plane-strain centrifuge models, tunnel volume loss can be simulated in a variety of ways, but is conventionally done using a fluid-filled flexible membrane or a rigid boundary mechanical model tunnel. The choice of model tunnel has an impact on the imparted tunnel boundary displacements and resulting ground deformations, yet a thorough quantitative evaluation of these effects has not been conducted. This paper aims to address this by contrasting plane-strain centrifuge test results from experiments using a flexible membrane model tunnel with those from a newly developed eccentric rigid boundary mechanical model tunnel. A quantitative assessment of surface and subsurface settlement trough characteristics as well as soil shear and volumetric response is provided. Results from numerical analyses using a hypoplastic constitutive model are also included, focusing on evaluating centrifuge spin-up effects and contrasting numerical outcomes with experimental data relating to settlement trough characteristics and soil shear/volumetric response. The outcomes of this paper should benefit future researchers considering which type of model tunnel to adopt when developing centrifuge tests related to 2D plane-strain tunnel modelling.